PA.02 Operative skills training in obstetrics – identification of increased training needs for junior doctors. (9th June 2014) - Aiken, CE; Park, H; Brockelsby, J; Prentice, A
Abstract : Introduction: Reduced working hours have caused concern regarding adequate training of junior doctors. An experience gap between basic and intermediate level training in obstetrics has been recognised. We compared experience between ST2 (specialty trainee year 2; basic training) and ST3 (specialty trainee year 3; intermediate training), and investigated whether greater experience at ST2 improves performance at ST3. Methods: All operative deliveries by ST2/ST3 doctors at a UK tertiary obstetrics centre (2008–2012 inclusive) were examined. The outcomes of deliveries at ST2 v. ST3 were compared. The deliveries were compared using multiple logistic regression analysis. Results: ST2 doctors performed 753 operative deliveries, compared to 1405 by ST3 doctors. The average number of emergency caesarean sections performed increased by over 600% between ST2 and ST3 (14.4 ± 4 v. 91.45 ± 11). Adverse outcomes were more common after deliveries by ST3s compared to the unit overall (p < 0.01) indicating an unmet training need for ST3s. Increased number of deliveries at ST2 level correlated with better performance at ST3 level (less blood loss at caesarean section p < 0.05; more successful instrumental deliveries p < 0.05; and a trend towards fewer critical incidents at delivery p = 0.07). The materno-fetal characteristics of the deliveries performed by ST2 and ST3 doctors did not vary significantly. Conclusions: Training currently available at ST2 level does not adequately prepare junior doctors for working at ST3 level. Doctors who undertook more operative deliveries at ST2 performed better than their peers at ST3. Maximising the experience that ST2s get on delivery units could help optimise their outcomes at ST3.